Farmers Empowerment: Drivers and Challenges among Smallholder Farmers in Mezam Division, Cameroon - Nganje Sophie Nanyongo; Wirbam Mary-Juliet Bime (International Journal of Business Economics (IJBE), 2022)
This study is captured: Farmers Empowerment: Drivers and Challenges among smallholder farmers in Mezam Division, Cameroon. The objectives targeted are: to identify and discuss the drivers and constraints associated with farmers empowerment in Mezam Division, Cameroon and to decompose the factors into gender of household head. Methodologically, the study employed primary data collected among 361 farmers using a well-structured questionnaire. The Cobb Douglas production function is used to estimate the result. In overall, farm experience, rich farmers financial status, acquisition of modern equipment, urban resident, age of farmers, land tenure system, household size and farm records are observed to be significantly influencing farmers empowerment in Mezam Division. Meanwhile rich farmers status, size of farm land, acquisition of modern equipment, farm records and household size are corroborating with the empowerment of male farmers and rich farmers status, acquisition of modern agricultural equipment and household size are positively influencing the empowerment of female farmers. The challenges faced by farmers in the acquisition of empowerment in Mezam are observed to be: training cost, access to trainers, source of training program, time constraint, application of training techniques, interest of farmers and ignorance. The study suggest that the decision makers should consider the collective farmers characteristics when planning for farmers empowerment. This is an important step towards farm efficiency and poverty alleviation.